2017
DOI: 10.1128/aac.02574-16
|View full text |Cite
|
Sign up to set email alerts
|

Troponoids Can Inhibit Growth of the Human Fungal Pathogen Cryptococcus neoformans

Abstract: Cryptococcus neoformans is a pathogen that is common in immunosuppressed patients. It can be treated with amphotericin B and fluconazole, but the mortality rate remains 15 to 30%. Thus, novel and more effective anticryptococcal therapies are needed. The troponoids are based on natural products isolated from western red cedar, and have a broad range of antimicrobial activities. Extracts of western red cedar inhibit the growth of several fungal species, but neither western red cedar extracts nor troponoid deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…2). Lactonization of #107 to 280 was reported by our labs previously, and was found to take place under fairly mild conditions (0.05% trifluoroacetic acid in water/acetonitrile) (Donlin et al, 2017). Here, we suggest that this lactonization (between #107 to 280) may take place in cell cultures.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…2). Lactonization of #107 to 280 was reported by our labs previously, and was found to take place under fairly mild conditions (0.05% trifluoroacetic acid in water/acetonitrile) (Donlin et al, 2017). Here, we suggest that this lactonization (between #107 to 280) may take place in cell cultures.…”
Section: Resultsmentioning
confidence: 68%
“…Compounds #106–120, 143–147, 273–274, and 335 were synthetized from kojic acid as previously described (D'Erasmo et al, 2016; Hirsch et al, 2014; Ireland et al, 2016; Meck et al, 2012; Williams et al, 2013). Compounds #280, 308–313, 315, and 317–319 were synthesized as described (Donlin et al, 2017). Compounds #261–264 were made using the Banwell method (Banwell et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…The contiguous array of at least three oxygen atoms (ketone/hydroxyl) and the sevenmembered aromatic ring are both essential for the broad bioactivities of compound 1 (6,7). Interest in the potential bioactivities and unusual structure of compound 1 has generated a number of chemical synthesis studies focused on the derivatization of tropolone, as well as studies supporting tropolone as a very promising therapeutic drug lead (2,(8)(9)(10).…”
mentioning
confidence: 99%
“…The tropone ring has a unique structure and properties and despite their non-benzenoid nature, they are planar and possess aromatic character. Natural and synthetic compounds that have the troponoid core have profound biological activities and have been used as antitumor, [1][2][3] antifungal, 4 and antimicrobial agents. 5 The biological activities of these compounds has been mainly attributed to their inhibitory effect on bimetallic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This antibiotic was found to exhibit antibacterial, antifungal, and antiprotozoal activities in vitro. Recently, Donlin and coworkers 4 reported that thiotropolone 5 can inhibit the growth of the fungus Cryptococcus neoformans with a minimal 80% inhibitory concentration (MIC 80 ) of 0.25 mM. In our effort to design and synthesize new thiotropolones to treat pathogenic fungi and multidrug resistant bacteria, we used the natural product b-thujaplicin (2) as starting point (Fig.…”
mentioning
confidence: 99%